K-file vs ProFiles in cleaning capacity and instrumentation time in primary molar root canals: An in vitro study - N Madan; A Rathnam; A L Shigli; K R Indushekar (Wolters Kluwer Medknow Publications, 2011)
Objectives: This study compares the efficiency of manual K-files and rotary ProFiles in cleaning capacity and instrumentation time in primary molar root canals. Materials and Methods: Seventy-five maxillary and mandibular primary molar root canals were instrumented with ProFiles and K-files in the step-back manner from size #10 to #40. The teeth were decalcified, dehydrated and cleared, and analyzed for the presence of dye remaining on the root canal walls, which served as an evidence of cleaning capacity of both the techniques. Results: The results showed a significant difference in the cleaning capacity of the root canals with ProFiles and K-files, in apical and coronal thirds of the root canal. ProFiles have been found to be more efficient in cleaning the coronal thirds and K-files in cleaning apical thirds of the root canals. Both the techniques were almost equally effective in cleaning the middle thirds of the canals. The time taken during the cleaning of the root canals appeared to be statistically shorter with K-files than profiles.